PRAKTIKALITAS MATERI AJAR KETERAMPILAN BERWAWANCARA BERBASIS TEKNIK TIRU MODEL DALAM GELAR WICARA TIPE LIGHT ENTERTAINMENT DI TELEVISI - Leona, Nindy; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of this study is to describe how the practicality of teaching materials for interviewing skills based on the model of imitation techniques in light entertainment type speech titles used by Indonesian Language Study Program students. This type of research is research and development. Research and development methods are research methods used to produce certain products and obtain the effectiveness of these products. The development model used is a 4-D model (define, design, develop, and disseminate). The type of data in this study is quantitative data. Quantitative data were obtained from the results of questionnaire practicality of teaching materials by lecturers and students. This research was conducted in the rhetoric class in July-December 2019 Indonesian Language Education study program, Faculty of Language and Art, Padang State University. The practicality of teaching materials is assessed from four aspects, namely presentation, ease of use, readability, and time spent. The results of this study indicate that teaching materials produced are categorized as practical. This practicality is seen from the practicality values obtained from lecturers 'and students' assessments. The practicality value of the lecturers is 88.89% with a very practical category. The practicality value of students is 82.64% with a very practical category. Based on this, the teaching materials for interviewing skills based on model copying techniques in the light entertainment type of speech degree have direct implications for the learning of interviewing skills. Kata Kunci: Praktikalitas, Materi Ajar, Keterampilan Berwawancara